[tex]\displaystyle\bf\\\left\{\begin{array}{ccc}-2x+3 \ , \ x\leq -2\\x^{2} -x+1 \ , \ -2 < x < 3\\3 \ , \ x\geq 3\end{array}\right \\\\\\1) \ \ -4 < -2 \ \ \Rightarrow \ \ f(-4)=-2\cdot (-4)+3=8+3=11\\\\\\2) \ \ -2=-2 \ \ \Rightarrow \ \ f(-2)=-2\cdot (-2)+3=4+3=7\\\\\\3) \ \ -2 < 1 < 3 \ \ \Rightarrow \ \ f(1)=1^{2}-1+1=1\\\\\\4) \ \ 3=3 \ \ \Rightarrow \ \ f(3)=3\\\\\\5) \ \ 4,9 > 3 \ \ \Rightarrow \ \ f(4,9)=3[/tex]
Ответ:
Объяснение: дивись розвязування в файлі нижче.
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
[tex]\displaystyle\bf\\\left\{\begin{array}{ccc}-2x+3 \ , \ x\leq -2\\x^{2} -x+1 \ , \ -2 < x < 3\\3 \ , \ x\geq 3\end{array}\right \\\\\\1) \ \ -4 < -2 \ \ \Rightarrow \ \ f(-4)=-2\cdot (-4)+3=8+3=11\\\\\\2) \ \ -2=-2 \ \ \Rightarrow \ \ f(-2)=-2\cdot (-2)+3=4+3=7\\\\\\3) \ \ -2 < 1 < 3 \ \ \Rightarrow \ \ f(1)=1^{2}-1+1=1\\\\\\4) \ \ 3=3 \ \ \Rightarrow \ \ f(3)=3\\\\\\5) \ \ 4,9 > 3 \ \ \Rightarrow \ \ f(4,9)=3[/tex]
Ответ:
Объяснение: дивись розвязування в файлі нижче.